Changing patterns of marine resource exploitation by hunter-gatherers throughout the late Holocene of Argentina are uncorrelated to sea surface temperature - Saporiti, F. (2013)
During the late Holocene, the coastal marine resources of southern South America were exploited by both marine hunter-gatherers with aquatic mobility in the Beagle Channel and the Chilean archipelago and terrestrial hunter-gatherers who inhabited various coastal settings in Argentina. Although the two cultures differed in technology and in historical exploitation patterns, they both used otariids, molluscs, fishes and sea birds as sources of food and raw materials for centuries. Ultimately, their use of these resources, particularly of otariids, declined strongly at different times. Overexploitation has been suggested as the main reason for this pattern, at least in the Beagle Channel, but similar declines in the north Pacific have been attributed to an increase in sea surface temperature (SST). The present paper tests the latter hypothesis in southern South America by using the δ18 O of bivalve shells (Aulacomya atra atra and Mytilus edulis) collected at archaeological sites as a proxy for SST and comparing the patterns of δ18O with the patterns of resource exploitation by hunter-gatherers. Samples were collected from the Beagle Channel and the central-northern Patagonian coast (north to 43° S) to generate two comparable datasets. The results suggest that SST increased in both areas at the beginning of the late Holocene and was slightly higher than at present during most of that period, except during the Little Ice Age, when values similar to those recorded at the end of the middle Holocene were found. The relative importance of otariids, mainly Arctocephalus australis, in the economy of the inhabitants of the Beagle Channel declined as SST increased, but otariid exploitation did not intensify again during the Little Ice Age. On the contrary, the intensity of otariid exploitation in central-northern Patagonia, mainly Otaria flavescens, was unrelated to the changes in δ18 O. Thus, changes in SST are unlikely to be the major driver of these resource-exploitation patterns.